Coronary Artery Bypass Surgery in Patients Receiving Dual Antiplatelet Therapy and the Impact of Preoperative Vitamin D Levels During COVID-19 Pandemic: An Observational Single Center Study - Meral Ekim; Sameh Alagha (Genel Tıp Dergisi)
Background: The COVID-19 pandemic has led to a surge in catheter-based interventions as elective surgeries were postponed. However, there has been a simultaneous rise in emergency CABG surgeries due to stent thrombosis or catheter-related complications. The potential impact of vitamin D on the immune system has also gained attention during the pandemic. We aim to investigate the impact of preoperative dual anti-platelet (DAPT) usage and vitamin D levels of those patients who underwent CABG on postoperative outcomes. Materials and methods: This retrospective study was conducted between March 23, 2020, and December 30, 2021. The study included 63 patients who underwent elective and emergency CABG while on dual antiplatelet therapy, d vitamin levels were obtained from all the patients preoperatively. Results: 51 of the 63 patients were males and 12 were females. The mean age was 62.69 ± 8.43 years. 15 patients (24%) were on Clopidogrel and Acetylsalicylic acid (ASA) and 48 patients (76%) were on Ticagrelor and ASA preoperatively. Off-pump CABG was performed in 21 patients (33%). One patient had a stroke (1.6 %). The amount of drainage was significantly higher in patients using Ticagrelor and (ASA) (p=0.015). The mean vitamin D level was 13.94±5.24 ng/ml ranging from 3.38 ng/ml to 24.99 ng/ml, Vitamin D levels were significantly lower in female patients compared to males (p=0.004). Conclusion: CABG surgery in patients receiving DAPT presents unique challenges and requires careful management to minimize bleeding complications. Additionally, maintaining adequate vitamin D levels preoperatively may improve postoperative outcomes.